Proofing Tools in Microsoft Office Word 2019: The Application in Indonesian Language - Arief Fiddienika (TEKNOSASTIK, 2020)
Microsoft Office Word 2019 has grammar correction in various languages, one of which is Indonesian. This paper aims to explore the features of the spelling and inspection tools of Microsoft Office Word 2019. This verification tool was tested with Indonesian linguistic units, compound words, affixes, and particles. In addition, the testing was also carried out on Indonesian punctuation. From this research it was found that the Microsoft Office Word 2019 system proofing tools only works best when errors occur in words and reduplication. This tool cannot detect errors in using punctuation, errors at the syntactical level and at the semantic level. The realm of sentences and meanings did not pass this test.